The Influence of Murabahah Financing on the Financial Performance of Islamic Banks in Indonesia: An Empirical Analysis - Ridho, Ridho Kurniawan; Najwa, Najwa Shifa Qursya (Alhamdulillah : Jurnal Agama Islam, 2024)
This study aims to analyze the effect of murabahah financing on the financial performance of Islamic banks in Indonesia. Using secondary data from Islamic bank financial reports for the period 2018-2022, this study applies multiple linear regression analysis to test the relationship between murabahah financing and financial performance variables such as profitability, operational efficiency, and asset growth. The results of the study indicate that murabahah financing has a significant positive effect on profitability and asset growth, while its effect on operational efficiency is more moderate. Murabahah financing has proven to be an effective instrument in improving the financial performance of Islamic banks, both in terms of stable income and cost efficiency. This study provides insight for Islamic banks to further develop murabahah financing strategies by considering risk management and diversification of financing products.